Efficacy evaluation of Mohlolo Insecticide Bait on German Cockroach, Blattella Germanica L - Mbowane, Clarah (My University, 2014)
In most cases the discipline plant protection is restricted to the protection of propagules, the plants and their produce in storage, while excluding the protection of processed (cooked) food from contaminants. Generally, the German cockroach (Blattella germanica L.) is a serious contaminant of processed food and had recently been viewed as a pest worthy of control in plant protection when viewing the entire value chain of agricultural commodities. Due to the nature of the pest, it is quite difficult to control using registered agrochemicals on the market. An entrepreneur in the rural areas of Limpopo Province developed bait for cockroach control, which was code named Mohlolo during efficacy trials. The use of baiting in cockroach management is currently the sought after approach in the world where cockroaches are problematic. Bait has the advantage over liquid or dust formulations because baiting requires shorter service, has shown increased efficacy, and has reduced environmental contamination. The objectives of this study were to determine whether the effect of MIB would be age related in the suppression of populations of B. germanica under laboratory conditions, and also to investigate whether MIB would reduce populations of B. germanica in residential areas. Five concurrent B. germanica age-related experiments were run in a complete randomized design. 1-d, 2-d, 3-d, 4-d, 5-d old nymphs and adult German cockroach experiments were conducted at Limpopo Agro-Food Technology Station (LATS) laboratory, (53’21,41” S/29 23o 44’19,95”E) hosted at the University of Limpopo. Each age group consisted of 10 nymphs and was put in 250 cm3 container that contained xv Mohlolo insecticide bait (MIB). One gram (1 g) of Mohlolo insecticide bait and moistened cotton wick were put at the bottom centre of the 250 cm3 containers containing nymphs based according to their respective ages. Residential experiments were conducted at UL student apartments. Two Bait containers were then placed in the kitchen, lodge, bathroom and bedroom. In the kitchen MIB containers were put behind the cooking stove and refrigerator, in the lodge the bait was placed next to the study table (because most study tables are also used during the eating time). In the bathroom the baits were put next to toilet seat and lastly in the bedroom, the bait was placed next to study table. According to the results, 100% mortality of 1-, 2-, 3-, 4-, 5-days nymphs and adult B. germanica was obtained after 7th, 2nd 3rd 3rd and 4th day, whereas LT50 values ranged from half a day to one and half (1.5) day. The study also demonstrated that B. germanica populations had high LT50 and LT100 values in residential areas compared to LT50 and LT100 values obtained in the laboratory experiments. This is probably due to the fact that residential areas that have low levels of sanitation availed the cockroaches with an opportunity to choose from many foods hence, it reduced the probability for cockroaches to feed on Mohlolo insecticide bait in the respective apartments. Results of this study showed that, Mohlolo bait toxicity and effectiveness as a control agent can reduce infestation of cockroaches in all developmental stages when applied at small quantity. Providing results of this study would provide information on resistance and tolerance of B. germanica nymphs and adult population against MIB in the xvi laboratory and residential areas. It would also provide biological information on the efficacy of MIB against the German cockroaches.
Thesis (M.Sc. (Plant Production)) -- University of Limpopo, 2014
Keywords: German cockroach; Insecticides; Insecticides.; Pests -- Control.; Insect baits and repellents.; Insects as carriers of disease.